PEMANFAATAN DIGITAL MARKETING SEBAGAI STRATEGI KOMUNIKASI PEMASARAN EFEKTIF DAN INOVATIF UNTUK MENARIK KONSUMEN UMKM - Astikarani, Ni Made Dhyana; I Komang, Yasa Widya Purnama (Waisya : Jurnal Ekonomi Hindu, 2024)
Digital marketing has become an increasingly important strategy for Micro, Small and Medium Enterprises (MSMEs) in an effort to attract and retain consumers in the digital era. This research examines the use of digital marketing as an effective and innovative marketing communications strategy to support the growth of MSMEs. The research method uses a qualitative descriptive approach with primary data sources obtained from King Kebab MSME consumers and social media activities. The research location is in Mataram City, specifically King Kebab MSMEs. Through the use of digital platforms such as social media and e-commerce, MSMEs can reach wider and more precisely segmented consumers, as well as convey relevant and personal messages to consumers. Even though King Kebab MSMEs often face challenges such as limited resources, low digital literacy, and intense competition, digital marketing strategies that are tailored to the characteristics of target consumers can produce more optimal results compared to conventional marketing methods. This research aims to discuss the level of understanding and application of digital marketing by MSMEs in marketing communication strategies, the challenges faced by MSMEs in utilizing digital marketing to attract consumers, the effectiveness of digital marketing in increasing consumer attraction and loyalty to MSMEs compared to conventional marketing strategies, and MSMEs can develop digital marketing strategies that are innovative and suit the characteristics of target consumers. Highlighting the importance of innovation and the use of technology in digital marketing strategies to increase consumer attraction and loyalty, as well as support the sustainability of MSME businesses in an increasingly competitive market.